Linking C&I to a code of practice for industrial tropical tree plantations - Poulsen, J.; Applegate, G.; Raymond, D. (Center for International Forestry Research, 2001)
Over the last ten years there has been an increasing emphasis on development of plantation estates for both wood fiber and agricultural crops such as oil palm. The principles for sustainable development and establishment of industrial plantations also account for the social, environmental and biodiversity aspects.This document showed the first attempt of CIFOR to develop a process designed to link the development of criteria and indicators (C&I) more closely with practical and sustainable plantation development principles and practices, the latter expressed through a Code of Practice. To ensure that the two systems are mutually compatible they have been developed simultaneously. The process aims to ensure that the satndards for practical development of industrial plantations reflect, properly and appropriately, the needs and concerns expressed in the criteria and indicators for sustainable management and development of planted forests. This is intended to both increase the relevance and hence perhaps the adoption of C&I, such as those developed by CIFOR. Criteria and indicators can provide the benchmark for a plantation owner to assess progress towards sustainable forest management within their forest estate.It can be used as a means of assesing compliance with suitable set of benchmarks such as contained within a Code of Practice for industrial tree plantation development in the tropics (Code). (YS)